2021
DOI: 10.18805/lr-577
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Five Legume Species under Drought Conditions

Abstract: Background: Vegetative, reproductive and grain-filling phases are critical developmental stages determined legume’s yield and grain quality. Drought is the key factor affecting legumes ontogeny and production. The main goal of the present study is to compare growth, yield and seed quality of different legume species grown under drought conditions. Methods: Completely randomized design were used in this experiment with five local legume species including faba bean, chickpea, lentil, common vetch and bitter vetc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, weak correlations between seed yield under irrigated condition and drought stress indicate presence of independent factors regulating yield performance under these conditions. This insignificant association of seed yield under the stress and optimal conditions in our study are consistent with the findings of many previous works [44]. The strong correlations between seed yield and the days to flowering, SB, MSI and RWC, protein content and biomass in both the irrigated and stress treatments (p < 0.05) at vegetative and reproductive stages (Figure 3) demonstrate their use as selection indices for selecting promising genotypes under drought stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, weak correlations between seed yield under irrigated condition and drought stress indicate presence of independent factors regulating yield performance under these conditions. This insignificant association of seed yield under the stress and optimal conditions in our study are consistent with the findings of many previous works [44]. The strong correlations between seed yield and the days to flowering, SB, MSI and RWC, protein content and biomass in both the irrigated and stress treatments (p < 0.05) at vegetative and reproductive stages (Figure 3) demonstrate their use as selection indices for selecting promising genotypes under drought stress.…”
Section: Discussionsupporting
confidence: 92%
“…Our study indicated that DSI varied between the 40 genotypes, which is in agreement with numerous studies on different crops to differentiate the drought-tolerant and sensitive genotypes [21]. This index is recommended as the most reliable criterion for the identification of tolerant and sensitive genotypes at vegetative and post-vegetative stages [44]. This result was further supported by the results of Pearson's correlation coefficients, where DSI showed significant negative correlation with MSI, RWC, protein content, biomass and seed yield and significant positive correlation with CI and DM.…”
Section: Discussionsupporting
confidence: 90%
“…Screening and selection of desirable genotypes for drought tolerance is the first and foremost important step in pulse breeding program (Jincya et al 2019). It has been stated that drought is the most important factor limiting yield and quality in legume production (Basheer-Salimia et al 2021). Inexpensive and short-term studies are needed to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Drought is determined as an environmental factor that affects the fertility and productivity of plants (Bartels and Sunkar, 2005;Basheer-Salimia et al 2021). Plant growth, crop productivity and development of plants are restricted as a result of drought and insufficient irrigation.…”
Section: Introductionmentioning
confidence: 99%